Attitudes and Awareness about Basic Life Support among Medical School Students in Lahore (Journal of Rashid Latif Medical College, 2025)
Background: The WHO recommends that all healthcare professionals must be equipped with this basic emergency life-saving service and capability. It comprises essential techniques for maintain airway patency, breathing and circulation in life-threatening emergency situations such as drowning, choking etc.Objective: This study aims to assess the awareness, knowledge and attitudes of medical students regarding basic life support (BLS) in LahoreMethodology This was descriptive, cross-sectional quantitative study. A total of 300 MBBS students were recruited for this study. A structured pre tested questionnaire from previously published studies was utilized.Results: In total, 40% of the participants showed sufficient BLS knowledge (score ≥ 6/10). Clinical year students had a higher mean (5.9 ± 1.6) than pre-clinical students (mean 4.1 ± 1.8; p = 0.001). The mean attitude score was 4.2 ± 0.7 overall, reflecting a generally positive attitude toward learning BLS.Conclusion: The research concludes that although medical students in Lahore have very positive attitudes toward Basic Life Support, their knowledge and hands-on exposure in conducting BLS are low. This deficiency can be overcome by incorporating structured, hands-on, and frequent BLS training sessions into the MBBS course of study. Equipping students with BLS will not only augment their professional capacity but also help greatly to enhance out-of-hospital cardiac arrest and other emergency survival rates in Pakistan.